THE URGENCY OF ELECTRONIC KNOW YOUR CUSTOMER (E-KYC): HOW ELECTRONIC CUSTOMER IDENTIFICATION WORKS TO PREVENT MONEY LAUNDERING IN THE FINTECH INDUSTRY - Ahmad Ghozi (Fakultas Hukum, Universitas Diponegoro, 2022)
The development of the Financial Technology (FinTech) Industry in Indonesia is very rapid. Financial Technology (FinTech) can generally be defined as an industry that combines technology and financial features as its business model. One of the advantages FinTech business is the speed and convenience for parties to conduct transactions. The speed and simplicity of transactions in the FinTech business are due to the use of technology in the financial services provided. Furthermore, the FinTech industry facilitates parties to conduct non-face-to-face transactions. The advantages offered by the FinTech industry raise concerns that this business could be used by criminals to commit money laundering crimes. This research tries to see the vital role of using Know Your Customer (KYC) customer principles which are carried out electronically to be applicable in preventing FinTech businesses from being used as a means of committing money laundering crimes.